LOBOLA (BRIDE PRICE) CULTURE AND THE EQUALITY OF WOMEN IN ZIMBABWE (The Pretoria Student Law Review, 2021)
This paper seeks to examine the effects of lobola custom on the status of women and their right to equality. It argues that lobola creates a hierarchy in the marriage institution which forms the basis for unequal power relations between husbands and wives. In its form and procedure, lobola perpetuates the subjugation of women to men. Women are subjected to control by men. This violates equal rights enshrined in Section 56 of the Constitution of Zimbabwe, Amendment (No 20) Act, 2013 (hereinafter referred to as 2013 Zimbabwean Constitution).
Keywords: Zimbabwe; lobola; women; unequal power relations; right to equality